2013
DOI: 10.1088/0957-4484/24/35/355602
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of silver and silver sulfide nanocrystals via selective cleavage of chemical bonds

Abstract: A one-step colloidal process has been adopted to prepare silver (Ag) and silver sulfide (Ag₂S) nanocrystals, thus avoiding presynthesis of an organometallic precursor and the injection of a toxic phosphine agent. During the reaction, a layered intermediate compound is first formed, which then acts as a precursor, decomposing into the nanocrystals. The composition of the as-obtained products can be controlled by selective cleavage of S-C bonds or Ag-S bonds. Pure Ag₂S nanocrystals can be obtained by directly he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 48 publications
4
19
0
5
Order By: Relevance
“…The ratiometric thermal sensitivity of the here‐reported Ag/Ag 2 S NCs is comparable to the highest thermal sensitivities reported for the widely used erbium‐based RLNThs, with the advantage of operating in the II‐BW, a requisite for subtissue thermal sensing. Furthermore, when comparing with other RLNThs also operating in the II‐BW, it is found that the here‐reported NCs provide thermal sensitivities several times higher than those of rare earth‐based systems such as Nd:LaF 3 NPs or Nd:Yb core/shell nanostructures (both having thermal sensitivities well below 1% °C −1 ).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The ratiometric thermal sensitivity of the here‐reported Ag/Ag 2 S NCs is comparable to the highest thermal sensitivities reported for the widely used erbium‐based RLNThs, with the advantage of operating in the II‐BW, a requisite for subtissue thermal sensing. Furthermore, when comparing with other RLNThs also operating in the II‐BW, it is found that the here‐reported NCs provide thermal sensitivities several times higher than those of rare earth‐based systems such as Nd:LaF 3 NPs or Nd:Yb core/shell nanostructures (both having thermal sensitivities well below 1% °C −1 ).…”
Section: Resultssupporting
confidence: 68%
“…The X‐ray energy dispersive spectroscopy (EDS) mapping images shown in Figure c–f reveal the presence of an Ag‐rich core surrounded by a Ag 2 S stoichiometric shell. The presence of this structure may result from the low reduction potential of the Ag + ions and the presence of thiols that can act as reducing agents in addition to their role as ligands …”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned results indicate that Please do not adjust margins Please do not adjust margins the presence of toluene in the organic phase has a significant effect on the formation of Ag2S and Ag nanocrystals, which is consistent with our previous work through a simple heat-up approach. 22 . As stated in our previous work, the Ag2S and Ag nanocrystals can be controllable synthesized by varying the dosage of DDT, which has a vital effect on the cleavage of S-C and Ag-S. 22 Similar to the case of djurleite nanocrystals synthesized with and without toluene the introduction of toluene in the reaction system could decrease the amount of DDT on the water/oil interface, the cleavage of Ag-S bond is preferential.…”
Section: Resultsmentioning
confidence: 99%
“…22 . As stated in our previous work, the Ag2S and Ag nanocrystals can be controllable synthesized by varying the dosage of DDT, which has a vital effect on the cleavage of S-C and Ag-S. 22 Similar to the case of djurleite nanocrystals synthesized with and without toluene the introduction of toluene in the reaction system could decrease the amount of DDT on the water/oil interface, the cleavage of Ag-S bond is preferential. Otherwise, the nucleophilic attack of DDT takes place, which leads to the cleavage of S-C, resulting the formation of Ag2S nanocrystals.The absorption spectra shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…В качестве функциональных материалов они нашли широкое применение в оптоэлектронике, сен-сорной технике и энергетике. Сульфид серебра Ag 2 S является одним из наиболее востребованных полупро-водниковых сульфидов [1][2][3], однако имеющиеся све-дения о строении и свойствах нанокристаллического сульфида серебра ограничены и не всегда однозначны. Особенно это относится к нанопорошкам и наночасти-цам Ag 2 S, потенциальное применение которых в мик-роэлектронике, биосенсорике и фотокатализе наиболее перспективно.…”
Section: Introductionunclassified